IMPLEMENTASI JANJI PERKAWINAN BA IMPLEMENTASI JANJI PERKAWINAN BAGI PASANGAN SUAMI-ISTRI USIA PERKAWINAN MADYA DALAM HIDUP BERKELUARGA DI PAROKI SANTA MARIA PONOROGO - Kurniawan, Andi; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2019)
The promise of a Catholic marriage is a promise made by a man and a woman who cannot be recanted and validated by God in the sacrament. In the promise of marriage, a married couple is united by God for life and are required to implement those promise in a family life. In implementing the marriage promise, couples often meet kinds of challenges. The study is aimed to know the implementation of marriage promise to a family life. The study used qualitative methods. The respondents were middle married couples who have been 6– 12 years old of marriage at Santa Maria Parish Ponorogo. Objective of the study were the meaning of marriage promise for middle married couples and the implementation of marriage promise for middle married couples. The results of this study were all of those respondents were able to live up their Catholic marriage promises and implement them. With respect to the implementation of the Catholic marriage promise, middle age marriage couples have a way to express their love and love each other,age such as cooperation, communication, genuine acceptance of one another, comforting and faithful. Middle age marriage couples also strive to build purely and totally love as genuine acceptance.